Interleukin-6: evolving role in the management of neuropathic pain in neuroimmunological disorders - Kenichi Serizawa; Haruna Tomizawa-Shinohara; Shota Miyake; Kenji Yogo; Yoshihiro Matsumoto (BMC, 2021)
Abstract Background Neuropathic pain in neuroimmunological disorders refers to pain caused by a lesion or disease of the somatosensory system such as multiple sclerosis (MS) and neuromyelitis optica spectrum disorder (NMOSD). MS and NMOSD are autoimmune disorders of the central nervous system, and ≥ 50% of patients with these disorders experience chronic neuropathic pain. The currently available medications for the management of neuropathic pain have limited effectiveness in patients with MS and NMOSD, and there is an unmet medical need to identify novel therapies for the management of chronic neuropathic pain in these patients. In this review article, we summarize the role of interleukin-6 (IL-6) in the pathogenesis of MS and NMOSD and the ameliorative effects of anti-IL-6 therapies in mouse models of experimental autoimmune encephalomyelitis (EAE). Main body Intraperitoneal injection of MR16-1, an anti-IL-6 receptor (IL-6R) antibody, reduced mechanical allodynia and spontaneous pain in EAE mice, which was attributed to a reduction in microglial activation and inhibition of the descending pain inhibitory system. The effect of anti-IL-6 therapies in ameliorating neuropathic pain in the clinical setting is controversial; a reduction in pain intensity has been reported with an anti-IL-6 antibody in four studies, namely a case report, a pilot study, a retrospective observational study, and a case series. Pain intensity was evaluated using a numerical rating scale (NRS), with a lower score indicating lesser pain. A reduction in the NRS score was reported in all four studies. However, in two randomized controlled trials of another anti-IL-6R antibody, the change in the visual analog scale pain score was not statistically significantly different when compared with placebo. This was attributed to the low mean pain score at baseline in both the trials and the concomitant use of medications for pain in one of the trials, which may have masked the effects of the anti-IL-6R antibody on neuropathic pain. Conclusion Thus, anti-IL-6 therapies might have a potential to reduce neuropathic pain, but further investigations are warranted to clarify the effect of inhibition of IL-6 signaling on neuropathic pain associated with MS and NMOSD.